Penerapan Model Pembelajaran Kontekstual Berbantuan Komik Digital untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis Siswa - Latifah, Firyal Aulia Nurul; Jihad, Asep; Widiastuti A, T Tutut (Universitas PGRI Semarang, 2026)
This study aims to analyze the contextual learning model assisted by digital comics in improving students' mathematical concept understanding ability. Quasi-experimental method was chosen as the method used and involved 26 students of class VIII D and 23 students of VIII A MTs Miftahul Falah. The instrument in this study was a descriptive test of conceptual understanding ability that had been validated and tested for reliability, and analyzed for its discrimination power and level of difficulty so that it was suitable for use. Data analysis was carried out by testing assumptions and hypothesis testing. The results of the analysis using the t' test (t accent) obtained a Sig. (One-Sided) value of 0.0035 0.005, so H0 was rejected. Thus, the improvement in students' mathematical concept understanding ability using the contextual learning model assisted by digital comics was better than students using conventional learning.